Increasing Sago Flour Production Capacity Through Sago Drying Media - Acep Fatchuroji; Candra Agus Wahyudhi (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The production of sago flour by the numembo farmers group has great potential for improvement in both quality and quantity. To achieve this, an essential aspect that needs enhancement is the sago flour drying medium. Through the Community Partnership Program (PKM), the team and partners successfully increased the productivity of sago flour production with the aid of an improved sago flour drying medium, resulting in a twofold increase in output. The methods used in the PKM included socialization, training, and assistance. The numembo farmers group was involved in designing the sago flour drying equipment and participated in the evaluation of the trial runs. These activities provided benefits by boosting the productivity and quality of sago flour and strengthened the local economy by producing more competitive market products.